The Effectiveness of Group Counselling with Self Talk Technique and Combination of Self Talk and Reframing Technique to Reduce Aggressivity (Universitas Negeri Semarang, 2018)
This study aims to examine the effectiveness of group counseling with self-talk and combination of self talk & reframing techniques to reduce aggressiveness in students of SMP Muhammadiyah 6 Semarang. The research method used was experiment with randomized pretest-posttest comparison group design involving 14 subjects selected purposively from the total population of 117 students. The main instrument used is the Agression Questionnaire with the number of 29 items valid (rxy = 0.303 – 0.687) and reliability of 0.870. The treatment was given for 5 sessions for self talk and 5 sessions for self talk & reframing combination with 2x40 minute duration. Data analysis using wilcoxon and wallist cruciate test. The results showed the technique of reframing and self-talk effective to reduce aggressiveness of students of SMP Muhammadiyah 6 Semarang. Judging from the difference in effectiveness levels, self talk and self talk & reframing techniques show the same level of effectiveness. This study provides clarification of handling aggressiveness problem with self talk technique and combination of self talk & reframing technique.